Analysis of the Market of Energy Suppliers For Charging Electric Vehicles in Poland - Anna WIKTOROWSKA-JASIK; Joanna SEKand Magdalena KAUP (Communications of International Proceedings, 2024)
The main objective of the research contained in the article is to analyse the structure of the market of energy suppliers for charging electric vehicles in Poland. Currently, many scientific publications deal with the topic of electromobility from the point of view of the available infrastructure, however, the issues of energy suppliers for charging vehicles are neglected. Therefore, special consideration was given to introducing the most important entities operating on the Polish market in the context of an attempt to determine their market share and the scope of services offered. The first part of the article presents the current state of publicly available electric vehicle charging stations in Poland, along with a description of the most commonly used chargers. The year-on-year growth dynamics of publicly available charging points is presented. For example, comparing data for July of 2023 and 2024 in the year-on-year system, the increase was as high as 76%. In the second part of the article, a comparative analysis of energy suppliers in terms of their offer and capabilities was carried out, paying particular attention to the technical and organizational solutions they use. It was found that the market of energy suppliers focuses on the main five players. On the other hand, the market of operators, in addition to the three main players (ENEA, Orlen Charge and Tauron), is fragmented. Based on the analysis conducted, the dependencies and difficulties faced by energy suppliers to ensure an adequate level of service and the availability of charging infrastructure were identified.
Keywords: electromobility; energy suppliers; charging infrastructure; electric vehicles; electric vehicle charging system management